Design of Automatic Archivery Software to Easy Work System in Social Services - Zaid Kurnia; A H Qudsiah; H Nurhadi (International Journal of Research and Applied Technology (INJURATECH), 2023)
In the era of globalization, computer technology has an important role in assisting the process of work activities in agencies and offices, both from government and private institutions. The use of computer equipment as a supporting device for data management and processing is very appropriate with the consideration of computer equipment in any information that is needed in management or office activities. The purpose of this program is to facilitate data management of incoming and outgoing letters at the social service office still using manual methods in data input, in the office world the existence of information technology is also very useful for agencies to facilitate performance in daily activities, especially in managing mail data. incoming and outgoing letters. using qualitative research methods with literature study stage, software design stage using a programming language with flutter framework. The results of the software design that has been successfully created can be carried out in the testing phase or the implementation of the program application to see whether the program created can run according to the desired goal or not. The concept of this program is to change the manual system in filing letters to an automated system. The impact of this program is that it is hoped that the archiving of incoming and outgoing mail will be more effective and more structured. At the end of this program, it is hoped that outgoing and incoming letters will not be mixed and when looking for the required letters or documents it does not take a long time with the existence of this incoming and outgoing mail archiving software, making archiving more effective and more structured. With this software, it is easier for social service employees to process incoming and outgoing mail documents